Study on the Effects of Vermicompost on the Nodulation and the Yield of Chickpea - Bajracharya, Sanu K.; Rai, Suresh K. (Nepal Agriculture Research Journal, 2014)
Pot experiment was conducted in a randomized complete block design with three replication and six treatments in the screenhouse of Soil Science Division, Khumaltar during the year 2003 and 2004. The objective of the experiment was to find out the effect of vermicompost in combination with or without soil and mineral fertilizers on the yield and other attributes of chickpea. The results showed an encouraging effect of vermicompost application on the plant height, root length and biomass dry weight of chickpea when vermicompost was applied in equal ratio with soil (5 kg each/pot) and 10:20:15 kg N: P2O5:K2O kg ha-1. Vermicompost with equal ratio of soil (5 kg each/pot) also produced the highest mean grain yield of 10.6 gm per pot. However, no significant treatments effects were observed for root length and straw weights of the chickpea. Nepal Agric. Res. J. Vol. 9, 2009, pp. 49-55 DOI: http://dx.doi.org/10.3126/narj.v9i0.11641